Transcriptional Profiling of Testis Development in Pre-Sexually-Mature Hezuo Pig - Zunqiang Yan; Qiaoli Yang; Pengfei Wang; Shuangbao Gun (Current Issues in Molecular Biology)
Spermatogenesis is an advanced biological process, relying on intricate interactions between somatic and germ cells in testes. Investigating various cell types is challenging because of cellular heterogeneity. Single-cell RNA sequencing (scRNA-seq) offers a method to analyze cellular heterogeneity. In this research, we performed 10× Genomics scRNA-seq to conduct an unbiased single-cell transcriptomic analysis in Hezuo pig (HZP) testis at one month of age during prepuberty. We collected 14,276 cells and identified 8 cell types (including 2 germ cells types and 6 somatic cell types). Pseudo-timing analysis demonstrated that Leydig cells (LCs) and myoid cells (MCs) originated from a shared progenitor cell lineage. Moreover, the functional enrichment analyses showed that the genes of differential expression were enriched in spermatogonia (SPG) and were enriched in the cell cycle, reproduction, and spermatogenesis. Expressed genes in spermatocytes (SPCs) were enriched in the cAMP, cell cycle, male gamete generation, reproductive system development, and sexual reproduction, while growth hormone synthesis, gamete generation, reproductive process, and spermine synthase activity were enriched in Sertoli cells (SCs). Additionally, chemokine, B cell receptor, activation of immune response, and enzyme binding were enriched in macrophages. Our study investigated transcriptional alterations across different cell types during spermatogenesis, yielding new understandings of spermatogenic processes and cell development. This research delivers an exploration of spermatogenesis and testicular cell biology in HZP, establishing the groundwork for upcoming breeding initiatives.